Sailing: The crew leadership - Martinez-Moreno, A.; Morales-Baños, V.; Angosto Sánchez, S. (Journal of Human Sport & Exercise, 2018)
The aim of this study is to understand the type of leadership used by sailing crews. The sample consisted of a total of 45 subjects (97.8% men and 2.2% women), and the average age was 44.61 (±11,1) years old. A questionnaire about multifactorial leadership MLQ-5S (Bernard Bass & Bruce Avolio, 2000) was provided. It is formed by 45 items, from which 3 well-differentiated and non-exclusive leadership profiles can be obtained. The results show the crew of the racing sailing-boats had a transformational style of leadership (3.36 points), which was above of the transactional leadership and the style laissez faire or low leadership. As a conclusion, the type of leadership used by the sailing crew is transformational.